2014
DOI: 10.1563/aaid-joi-d-11-00163
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Microgap of Premade Abutments and Abutments Cast in Base Metal Alloys

Abstract: The study compared the marginal accuracy of premade and cast abutments. Premade titanium, stainless steel, and gold abutments formed the control groups. Plastic abutments were cast in nickel-chromium, cobalt-chromium and grade IV titanium. The abutment/implant interface was analyzed. Analysis of variance and Duncan's multiple range test revealed no significant difference in mean marginal microgap between premade gold and titanium abutments and between premade stainless steel and cast titanium abutments. Statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…This finding is in accordance with the results of Lalithamma et al (58) who found comparable results between ready-made titanium abutments and premachined cast gold with plastic sleeve abutments with no statistically significant difference between them.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in accordance with the results of Lalithamma et al (58) who found comparable results between ready-made titanium abutments and premachined cast gold with plastic sleeve abutments with no statistically significant difference between them.…”
Section: Discussionsupporting
confidence: 93%
“…Superior accuracy was observed between the original abutment and the implant in contrast with those found in the crown–implant and crown–abutment made from a cast component. Higher implant–abutment interface misfit has been reported when cast components are used (Lalithamma, Mallan, Murukan & Zarina, ). Rismanchian, Hatami, Badrian, Khalighinejad and Goroohi () compared different original abutments for Straumann implants, showing lower microgaps when abutments were machined than when they were cast.…”
Section: Discussionmentioning
confidence: 99%
“…Microgap sizes of the Morse taper connection at the implant–abutment joints measured in the present study ranged from 0.5 to 4.6 μm. Three previous studies reported the size of microgaps at the implant–abutment joints as follows: 0.75–15.48 mm,[ 12 ] 2–7 μm,[ 4 ] and 10–172 μm. [ 10 ] In addition, one study noted a rotational microgap component in degrees between abutment and implant hex from 1.21 to 2.79 degrees.…”
Section: Discussionmentioning
confidence: 99%
“…That study noted the mean marginal microgaps for cast abutments – 15.48 mm for Ni-Cr, 14.06 mm for Co-Cr, and 12.38 mm for Grade 4 titanium – versus those for milled abutments – 7.51 mm for Ti6Al4V, 13.51 mm for stainless steel, and 0.75 mm for gold. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%